Sensorineural hearing loss in Bartter syndrome - Semiramis Zizlavsky; Fadilah -; Ronny Soewento; Tri Juda Airlangga (Oto Rhino Laryngologica Indonesiana, 2021)
Background: Bartter syndrome is a rare inherited case characterized by autosomal recessive and has few different types. Diagnosis is established by laboratory findings, namely hypokalemic metabolic alkalosis, and normotensive. Hearing loss indicates Bartter syndrome type IV. Purpose: To report a case of Bartter syndrome with delayed speech. Case report: A seven years old girl with delayed speech and recurrent hypokalemia was referred to the Otolaryngology Head and Neck Surgery Department, Dr. Cipto Mangunkusumo Hospital, in order to evaluate the hearing level and treatment needed. Based on the Otoacoustic Emission (OAE), Brainstem Evoked Response Audiometry (BERA), and Auditory State Steady Response (ASSR), the diagnosis was profound bilateral sensorineural hearing loss and proceeded with hearing aid and also speech occupational therapy. Clinical question: Is there a relationship between Bartter syndrome and the incidence of hearing loss? Review method: Literature review through PubMed, Cochrane, and EBSCO, using keywords such as the impacts of Bartter syndrome on hearing loss, and sensorineural hearing loss in Bartter syndrome case. Result: Following screening of double publication and based on clinical questions over the past five years, only one relevant literature was found. Conclusion: Audiological assessment should be done in all Bartter syndrome’s cases. Early intervention and timely audiological rehabilitation could improve the quality of life of such children.ABSTRAK Latar belakang: Sindrom Bartter merupakan kasus jarang, yang diturunkan secara autosomal resesif dan terdiri atas beberapa tipe. Diagnosis ditegakkan berdasarkan temuan laboratorium yaitu hipokalemi, alkalosis metabolik dan tekanan darah normal. Adanya gangguan pendengaran merupakan sindrom Bartter tipe IV. Tujuan: melaporkan kasus Sindrom Bartter dengan keterlambatan bicara. Kasus: Dilaporkan satu kasus anak perempuan berusia tujuh tahun dengan gangguan bicara dan terdapat riwayat hipokalemia berulang yang dirujuk ke Departemen Telinga Hidung Tenggorok-Bedah Kepala Leher, Rumah Sakit Cipto Mangunkusumo untuk menilai ambang dengar serta tatalaksana selanjutnya. Berdasarkan hasil pemeriksaan Otoacoustic Emission (OAE), Brainstem Evoked Response Audiometry (BERA) dan Auditory State Steady Response (ASSR) ditemukan tuli sensorineural sangat berat bilateral yang kemudian ditatalaksana dengan pemakaian Alat Bantu Dengar dan terapi wicara dan okupasi. Pertanyaan klinis: Apakah ada hubungan antara sindroma Bartter dengan insidens gangguan pendengaran? Telaah literatur: Pencarian literatur melalui, PubMed, Cochrane dan EBSCO dengan kata kunci hubungan gangguan pendengaran pada sindrom Bartter, gangguan pendengaran sensorineural pada sindrom Bartter. Hasil: Setelah dilakukan skrining yakni publikasi ganda dan sesuai pertanyaan klinis dari lima tahun terakhir hanya didapatkan satu literatur yang relevan. Kesimpulan: Pemeriksaan pendengaran harus dilakukan pada kasus dengan sindrom Bartter. Intervensi dini dan rehabilitasi audiologi yang tepat waktu dapat meningkatkan kualitas hidup anak dengan sindrom Bartter.Kata kunci: sindroma Bartter, tuli sensorineural.